O Ecossistema manguezal em Meio Urbano no Contexto de Políticas Públicas de Uso e Ocupação do Solo na Bacia do Rio Anil, São Luis, Maranhão - Bezerra, Denilson da Silva (2008)
The ecosystem of mangroves possesses great relevance for the coastal area, fact that puts it as an intangible area for the juridical system of Brazil. However this, doesn't take into account the socioeconomic and real estate pressures imposed for this environment in the urban centers, appearing this way, paradoxical situations for the ecosystem, as well as, also, to the quality of human life. There for, the present study aims at to propose the insert of mangrove in municipal politics of use and occupation of the soil. For that, the scenery of the basin of the river Anil was used (São Luís-MA) in an interval of time from 1975 to 2001 with the aid of the geoprocessament tool. As result was obtained vectorial files of the alterations caused by the progress of the urban perimeter towards the environment object of the research (reduction of this around 35, 44%), as well as, estimate of this process in the neighborhoods of the Liberdade (R$ 20.560.400) and Jaracati (R$ 10.006.233). Being concluded this way that vectors socials, economicals and immobilities address the process of use of the environment focus of the present researches in the analyzed area.